Metode An-Nur sebagai Manajemen Pembelajaran untuk Membentuk Generasi Qur’ani - Muhammad Mushfi El Iq Bali; Siti Maisyaroh (LP2M STIT Palapa Nusantara, 2023)
This research is to find out the An-nur Method as learning management at the Tahfid An-nur Institute. This study aim is to reveal the planning, organizing, implementing, and evaluating learning. This study used a qualitative approach with a case study type, the research subjects consisted of heads of institutions, teacher and student. Research data obtained through in-depth interviews, observation, and documentation. Data analysis teachiques using data reduction, data presentation, and drawing conclusions. The results of the study found that learning management used the An-Nur Method at the Tahfidz An-Nur Institute consisting of steps. First, learning planning was carried out using teaching materials in the form of books prepared by the head of the institution. Second, the organization of learning is carried out by the head of the institution, namely in the form of organizing the division of teaching tasks for children, organizing material and allocating time. Third, the implementation of learning is carried out by managing activities, including opening, core activities, and closing. Fourth, the learning evaluation evaluates of learning conducts an assessment of the learning process in the form of memorization deposits carried out by the ustadzah by going through the learning outcomes that have been achieved by the children. The results of this assessment can be seen in the ability of the memorizers to keep the Al-Qur’an memorize, this can be determined by the Tahfid An-Nur Institute.